SNC1, a yeast homolog of the synaptic vesicle-associated membrane protein/synaptobrevin gene family: genetic interactions with the RAS and CAP genes. - Gerst, J E (1992)
SNC1, a gene from the yeast Saccharomyces cerevisiae, encodes a homolog of vertebrate synaptic vesicle-associated membrane proteins (VAMPs) or synaptobrevins. SNC1 was isolated by its ability to suppress the loss of CAP function in S. cerevisiae strains possessing an activated allele of RAS2. CAP is a component of the RAS-responsive S. cerevisiae adenylyl cyclase complex. The N-terminal domain of CAP is required for full cellular responsiveness to activated RAS proteins. The C-terminal domain of CAP is required for normal cellular morphology and responsiveness to nutrient extremes. Multicopy plasmids expressing SNC1 suppress only the loss of the C-terminal functions of CAP and only in the presence of activated RAS2.